The Ebony Column : Classics, Civilization, and the African American Reclamation of the West - Hairston, Eric Ashley (Book collections on Project MUSE., 2013)
In this book, the author begins a new thread in the conversation about the influence of Greek and Roman antiquity on U.S. civilization and education. The first book in the Classicism in American Culture series, this work demonstrates how the myths, cultures, and ideals of antiquity helped African Americans reconceptualize their role in a Euro-American world determined to make them mere economic commodities and emblems of moral and intellectual decay. To figures such as Wheatley, Douglass, Cooper, and DuBois, classical literature offered striking moral, intellectual, and philosophical alternatives to a viciously exclusionary vision of humanity, Africanity, the life of the citizen, and the life of the mind.